Semantic Predictability Facilitates Comprehension of Degraded Speech in a Graded Manner - Bhandari, Pratik; Demberg, Vera; Kray, Jutta (Frontiers in Psychology, 2021)
Previous studies have shown that at moderate levels of spectral degradation, semantic predictability facilitates language comprehension. It is argued that when speech is degraded, listeners have narrowed expectations about the sentence endings, i.e., semantic prediction may be limited to only most highly predictable sentence completions. The main objectives of this study were to (i)examine whether listeners form narrowed expectations or whether they form predictions across a wide range of probable sentence endings, (ii)assess whether the facilitatory effect of semantic predictability is modulated by perceptual adaptation to degraded speech, and (iii)to use and establish a sensitive metric for the measurement of language comprehension. We created 360 German Subject-Verb-Object sentences varying in semantic predictability of a sentence-final target word in a graded manner (high,mid,low) and levels of spectral degradation (1, 4, 6 and 8 channels noise-vocoding). These sentences were presented auditorily to two groups: One group(n=48) performed a listening task in an unpredictable channel context in which the degraded speech levels were randomized, while the other group(n=50) performed the task in a predictable channel context in which the degraded speech levels were blocked. The results showed that at 4 channels noise-vocoding, response accuracy was higher in high-predictability sentences than in the mid-predictability sentences, which in turn was higher than in the low-predictability sentences. This suggests that, in contrast to the narrowed expectations view, comprehension of moderately degraded speech, ranging from low- to high- including medium-predictability sentences, is facilitated in a graded manner; listeners probabilistically preactivate upcoming words from a wide range of semantic space, not limiting only to highly probable sentence endings. Additionally, in both channel contexts, we did not observe learning effects, i.e.,response accuracy did not increase over the course of experiment, and accuracy was higher in the predictable than in the unpredictable channel context. We speculate from these observations that when there is no trial-by-trial variation of the levels of speech degradation, listeners adapt to speech quality at a long timescale; however, when there is a trial-by-trial variation of the high-level semantic feature (e.g.,sentence predictability), listeners do not adapt to low level perceptual property (e.g.,speech quality) at a short timescale.